Diseño de un sistema de aprovechamiento de calor residual generado en el horno de secado de la empresa transformadores GVR Energy S.A.S. localizada en la ciudad de Ibagué. (2021)
This project carries out the design of a system to take advantage of the residual heat that is expelled during the gas combustion process in the drying oven on the production line of the transformers company GVR Energy S.A.S. (at 138 ° C) in order to reduce the energy consumption of the curing oven, since its heating operation is by means of 1200 Ohm electrical resistances (up to 120 ° C). Likewise, reduce the radiation from the drying oven that expels its combustion products into the environment and thus contribute to the improvement of the environment (about 22 tons of CO2 equivalent are no longer emitted into the atmosphere).